Aurora kinase-a expression heterogeneity and potential benefit of combination therapy in prostate adenocarcinoma - Chen, Ru; Qiu, Qianyi; Xie, Weiting; Lin, Jun; Liu, Rong; Chen, Jianhui; Zhu, Shaoxing; Su, Yiming (Frontiers in Cell and Developmental Biology, 2025)
BackgroundAurora kinase A (AURKA) is aberrantly expressed in a large number of tumors and promotes tumor progression by regulating the cell cycle, chromosomal instability, and drug resistance. However, its heterogeneous expression and combination therapy benefit in prostate adenocarcinoma (PRAD) is unclear.MethodsIn this study, we integrated TCGA pan-cancer multi-omics data and GEO data to analyze the RNA, methylation, protein expression, and genomic alteration characteristics of AURKA. We then used single-cell RNA sequencing to resolve the functional heterogeneity of AURKA in the PRAD epithelial cell subpopulation and verified its impact on the malignant phenotype of desmoplasia-resistant prostate cancer cells in in vitro experiments. This research also analyzed the prognostic risk stratification of AURKA subpopulations in combination with various indicators and the potential benefit of AURKA inhibitors in combination with various treatments.ResultsThe pan-cancer analysis demonstrated that AURKA expression heterogeneity was present among urological tumors at different molecular levels, and the positive correlation of AURKA alteration with MYC and E2F pathways was conserved in pan-cancer. Epithelial cell subpopulations with high expression of AURKA (epi3/4/6) promoted proliferation by regulating cell cycle and DNA repair, while low expression subsets (epi1/2/7) activated TNF-α and androgen receptor (AR) pathways to mediate drug resistance. In particular, AURKA may serve as a compensatory pathway to support tumor activity after AR inhibition in prostate cancer, a complex mechanism not seen in other tumors. AURKA-overexpressing patients with low Gleason scores or high PSA have a poor prognosis in clinical analysis. Furthermore, a comprehensive drug sensitivity co-analysis found that AURKA inhibitors may benefit from targeted therapy, ADC therapy, and immunotherapy. TMB and CD274 expression were the biomarkers of AURKA high-expression patients with PRAD for clinical outcome.ConclusionAURKA expression heterogeneity has been identified as a critical factor in the progression of PRAD and the development of drug resistance. The molecular subtyping of AURKA can serve as a precise strategy for combination therapy and provide a theory for the combination of AURKA inhibitors and targeted/immunotherapy.